2007
DOI: 10.1111/j.1742-1241.2007.01395.x
|View full text |Cite
|
Sign up to set email alerts
|

DXA scanning in women over 50 years with distal forearm fracture shows osteoporosis is infrequent until age 65 years

Abstract: Osteoporosis is infrequent in women with DFF below 65 years. As fracture prevention treatment yields significant fracture reduction only in patients with T-score < -2.5, DXA scanning below 65 years is not justified. After 65 years scanning is justified at all ages, as even in the elderly patients osteoporosis is present in < 50% of patients with DFF. Using nHanes III limits the number of DFF patients warranting treatment. Low body weight is unreliable for identifying osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The impact of low BMD in younger and older age groups is inconsistent in previous studies. In one small study, odds ratio for having low BMD were significantly greater in women younger than 65 years than in those aged 65 years and older presenting with a distal radius fracture [24] while, in another study, reduced BMD was more frequently seen in elderly distal radius fracture patients aged 65 years and older than in those younger than 65 years [40]. Contradictive results like this may be attributed to qualitative and quantitative differences between the examined cohorts as well as methodological discrepancies related to, e.g., patient recruitment and study design.…”
Section: Discussionmentioning
confidence: 96%
“…The impact of low BMD in younger and older age groups is inconsistent in previous studies. In one small study, odds ratio for having low BMD were significantly greater in women younger than 65 years than in those aged 65 years and older presenting with a distal radius fracture [24] while, in another study, reduced BMD was more frequently seen in elderly distal radius fracture patients aged 65 years and older than in those younger than 65 years [40]. Contradictive results like this may be attributed to qualitative and quantitative differences between the examined cohorts as well as methodological discrepancies related to, e.g., patient recruitment and study design.…”
Section: Discussionmentioning
confidence: 96%
“…The association of low BMD and age has been inconsistent in previous studies concerning distal radius fractures. 14,21 In one study, osteoporosis was found to be significantly associated with distal radius fracture only in women 65 years of age or less, 14 and in another study, a reduction in BMD was found to be more frequent in elderly patients. 21 However, the former of these studies used a small control group and the latter contained no control group.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies on osteoporosis rates in patients with a distal radius fracture differ in terms of the patient recruitment criteria and measurement methods used, which range from 37% to 51% (Table 3). 4,14,16 -18, 21 Hegeman et al 16 reported that the prevalence of osteoporosis was present in 51% of 94 women between 55 and 80 years of age (mean, 69 y) with a distal radius fracture, whereas Löfman et al 17 found a prevalence of osteoporosis of 37%.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations